2019
DOI: 10.1159/000495145
|View full text |Cite
|
Sign up to set email alerts
|

Position of Scientific Oncological Societies Towards Biosimilar Antibodies

Abstract: First biosimilars of monoclonal antibodies have recently been approved in oncology. Biosimilars enable economic competition, alleviate the financial burden for insurances, and may facilitate access to these drugs in low-income countries. Biosimilars are not completely identical to the original drug. The approval of biosimilars is only partially based on results of randomized clinical studies. In the introduction phase of new biosimilars, this can lead to uncertainties for patients and physicians. Based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 9 publications
0
8
0
3
Order By: Relevance
“…This showed that subsequently almost 80% of the oncology patients were able to answer correctly questions regarding marketing authorisation, reporting of side effects and cost management of biosimilars 27 . The German Society for Haematology and Oncology (DGHO) recommends dedicated briefing by the treating physician 28 . The European Society for Medical Oncology (ESMO) emphasizes the necessity of educating the prescribing physicians, nursing staff and patients in the use of biosimilars 14 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This showed that subsequently almost 80% of the oncology patients were able to answer correctly questions regarding marketing authorisation, reporting of side effects and cost management of biosimilars 27 . The German Society for Haematology and Oncology (DGHO) recommends dedicated briefing by the treating physician 28 . The European Society for Medical Oncology (ESMO) emphasizes the necessity of educating the prescribing physicians, nursing staff and patients in the use of biosimilars 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Since biosimilars are similar to the reference drug but – like different batches of the reference drug – are not identical, new side effects may arise. For example, increased immunogenicity caused by altered glycosylation or an increase in neutralising antibodies may occur 28 . In our surveyed centres, side effects with the biosimilar therapy essentially corresponded to the adverse drug reactions described in the Summary of Product Characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations